Análise de mapas conceituais elaborados por alunos da oitava série do ensino fundamental a partir de aulas pautadas na teoria da aprendizagem significativa : a argila como tema de estudo - Lourenço, Ariane Baffa (Universidade Federal de São Carlos, 2008)
In this work we analyze how and where extension student of the eighth series of the basic education of two public schools of the city São Carlos, conceptual maps from theoretical and experimental lessons elaborate, based in the theory of the Significant Learning, having as study subject the material clay. For the accomplishment of the research an initial study of characterization of two types of school clay was made, a white and another red. The results of this study had served as base for the elaboration of the course Clay, given in the regular period of lessons, in real situation of education in room. As instrument of evaluation of the learning reports and text had been used to elaborate by the students, questionnaire and conceptual maps. For the results we had that the use of texts and lessons elaborated based in the theory of the Significant Learning and the use of conceptual maps had assisted the learning of the students. The conceptual map was an efficient tool in the teach-learning process, therefore it allowed the students to identify and to relate the concepts between itself, and with too much concepts and examples, already existing in its cognitive structure, and to get a panorama of as its knowledge was structuralized. For the researcher, the map made possible to identify mistake ideas of the students, being able these to be worked individually, besides serving as evaluation instrument. For the results gotten in this work we evidence that it is possible to the teacher to use conceptual maps in its lessons, because this is a tool that assists in the process of teach-learning of the students, can be used as evaluation instrument and has good acceptance for the students.
Keywords: Aprendizagem significativa; Mapas conceituais; Ensino de Ciências; Argila; CIENCIAS HUMANAS::EDUCACAO